EXPERIENCE REPORT: PLAYING IS LEARNING-GAMES AND AFRICAN GAMES (Fiep Bulletin - online, 2017)
From the junction of the monograph entitled the BLACK BODY CULTURE in SCHOOL PHYSICAL EDUCATIONpresented to obtain the Bachelor degree in pedagogy in 2013, that provides the part of theoretical contextualization of this articleand of pedagogical intervention entitled PLAYING IS LEARNING-GAMES AND AFRICAN GAMES. (2015) based on jokes fromthe book Ndule ndule of Rógerio Andrade Barbosa, we built this article. Participated in this project (f) children of a class of firstyearelementary State school students 28 totaling Antônio de Oliveira Bueno Filho peripheral region of the city of Araraquara. Allof them were interviewed to obtain information about their knowledge on the subject. Our objective was: to enable our students:learn games of African origin and burst with negative images forged by different media, against blacks. To start the project thestudents answered the questions for the survey of the previous knowledge of the same regarding the theme to be addressedduring classes in this project that pointed to stereotyped knowledge on the African continent, as well as the lack of identificationand knowledge of games and games from there. Although in the descriptions and observations have not expressed any commentregarding étnicorraciais relations these took place yes. The jokes and games in ways subtle and inside her playfulness got thestudents valorize the difference of each other and brought unstressed your curiosity. The application and experience weresignificant for the construction of an identity that respects others and himself.